Surprise Questions for Survival Prediction in Patients With Advanced Cancer: A Multicenter Prospective Cohort Study. (8th June 2015) - Hamano, Jun; Morita, Tatsuya; Inoue, Satoshi; Ikenaga, Masayuki; Matsumoto, Yoshihisa; Sekine, Ryuichi; Yamaguchi, Takashi; Hirohashi, Takeshi; Tajima, Tsukasa; Tatara, Ryohei; Watanabe, Hiroaki; Otani, Hiroyuki; et al.
Abstract : Background: Predicting the short‐term survival in cancer patients is an important issue for patients, family, and oncologists. Although the prognostic accuracy of the surprise question has value in 1‐year mortality for cancer patients, the prognostic value for short‐term survival has not been formally assessed. The primary aim of the present study was to assess the prognostic value of the surprise question for 7‐day and 30‐day survival in patients with advanced cancer. Patients and Methods: The present multicenter prospective cohort study was conducted in Japan from September 2012 through April 2014, involving 16 palliative care units, 19 hospital‐based palliative care teams, and 23 home‐based palliative care services. Results: We recruited 2, 425 patients and included 2, 361 for analysis: 912 from hospital‐based palliative care teams, 895 from hospital palliative care units, and 554 from home‐based palliative care services. The sensitivity, specificity, positive predictive value, and negative predictive value of the 7‐day survival surprise question were 84.7% (95% confidence interval [CI], 80.7%–88.0%), 68.0% (95% CI, 67.3%–68.5%), 30.3% (95% CI, 28.9%–31.5%), and 96.4% (95% CI, 95.5%–97.2%), respectively. The sensitivity, specificity, positive predictive value, and negative predictive value for the 30‐day surprise question were 95.6% (95% CI, 94.4%–96.6%), 37.0% (95% CI, 35.9%–37.9%), 57.6% (95% CI, 56.8%–58.2%), and 90.4% (95% CI, 87.7%–92.6%), respectively. Conclusion: Surprise questions are useful for screening patients for short survival. However, the high false‐positive rates do not allow clinicians to provide definitive prognosis prediction. Implications for Practice: The findings of this study indicate that clinicians can screen patients for 7‐ or 30‐day survival using surprise questions with 90% or more sensitivity. Clinicians cannot provide accurate prognosis estimation, and all patients will not always die within the defined periods. The screened patients can be regarded as the subjects to be prepared for approaching death, and proactive discussion would be useful for such patients. Abstract : The present study assessed the prognostic value of the surprise question for 7‐day and 30‐day survival in patients with advanced cancer. Surprise questions are useful for screening patients with short survival. However, the high false‐positive rates do not allow clinicians to provide a definitive prognosis prediction.